مرزا محمد تقی خان ترقی: اردو کے ایک اہم کلاسیکی شاعر - Attique, Dr. Muhammad Akram (Zoraiz, 2022)
Delhi and Lucknow were two major centers of Urdu poetry. In Delhi, there was poetry full of emotions and feelings, while the poets of Lucknow paid attention to the reformation of language and expression and rendered special services in this regard. Mirza Muhammad Taqui Khan Taraqqui from Lucknow was a senior poet from Aatish and Nasikh. Expert style is reflected in his poetry. The principles that Nasikh had formulated for the reform of the language are seen to be followed by Taraqqui. A review of Mirza Taraqqui’s manuscripts shows that he had made obsolete the words which were rendered obsolete by the linguistic movement of Nasikh. A conscious and expert attempt to introduce several Urdu words can be seen in his verses. Words that have more than one meaning, Mirza Taraqqui has used them in his verses in such a way that their different meanings become clear. Mirza Taraqqui was the son-in-law of Nawab Siraj-ud-Daula and brother-in-law of Nawab Asif-ud-Daula. In this article, the circumstances and events of Mirza Muhammad Taqui Khan Taraqqui’s life have been researched.